RAMAN AND X-RAY FLUORESCENCE TO IDENTIFY COLORS OF THE GERMAN HYPERINFLATION STAMPS OF THE 1923 COLLECTION - Gómez-Jeria, J.S.; Campos-Vallette, Marcelo; Carrasco-Flores, E.A.; Gutiérrez V., S. (Journal of the Chilean Chemical Society, 2019)
Colors of a collection set of postage stamps dated 1923 and corresponding to the hyperinflationary period of the German economy were identifiedwith Raman and X-ray fluorescence (XRF) spectroscopies. Molecular systems associated to the blue, green and yellow colours were characterized. Blue colour is Prussian blue (Fe4[Fe(CN)6]3) and the green colour resulted to be a combination of Prussian blue and the yellow/orange pigment (PbCrO4) or a yellow β-naphthol like monoazopigment. The XRF data suggest that ZnO was used as filler.